BIBLIOMETRIC ANALYSIS OF LITERATURE REVIEW ARTICLES PUBLISHED BY MALAYSIAN AUTHORS - Khairul Hafezad Abdullah; Mohd Firdaus Roslan; Munirah Ilias (Jurnal Penyelidikan Sains Sosial, 2023)
more profound fathoming of the existing research’s concepts, methodology, and gaps will be obtained with scrupulous attention in conducting a literature review and systematically evaluating scholarly resources on a specific topic. This study examines the evolution and trends of literature review articles produced by Malaysian authors, identifies the ten most influential literature review articles, and investigates the nature of collaboration between Malaysian and international authors. Using VOSviewer and Publish or Perish (PoP), this study conducted a bibliometric analysis of 1,456 scholarly works pertinent to literature reviews in the Scopus database in December 2022. The number of publications remained constant between 1977 and 2008, with fewer than five articles published each year before beginning to increase in 2009. Since 2018, “systematic literature review”, “comprehensive literature review”, and “systematic review” have become popular strategies for creating literature reviews, as determined by analysing the text related to the titles. In the meanwhile, based on the text analysis of the abstract, this study revealed that the term “gap” is closely linked to “model”, “topic”, and “theory” literally. The article with the most citations is titled “Magnitude and risk factors for postpartum symptoms: a literature review”. There is no precise pattern for creating a literature review; nonetheless, most authors supplied a systematic writing process by including objectives or research questions in their introduction or background. Most prior researchers utilised the Scopus and Web of Science databases to gather articles for review purposes. Authors from Malaysia worked closely with authors from Saudi Arabia, India, Italy, the United Kingdom, and Germany. Researchers commencing academic writing will find this study an invaluable resource for writing literature reviews. They may utilise this information as an indirect source of motivation to help them compose a literature review.